2014
DOI: 10.1105/tpc.114.127993
|View full text |Cite
|
Sign up to set email alerts
|

TAA1-Regulated Local Auxin Biosynthesis in the Root-Apex Transition Zone Mediates the Aluminum-Induced Inhibition of Root Growth inArabidopsis     

Abstract: The transition zone (TZ) of the root apex is the perception site of Al toxicity. Here, we show that exposure of Arabidopsis thaliana roots to Al induces a localized enhancement of auxin signaling in the root-apex TZ that is dependent on TAA1, which encodes a Trp aminotransferase and regulates auxin biosynthesis. TAA1 is specifically upregulated in the root-apex TZ in response to Al treatment, thus mediating local auxin biosynthesis and inhibition of root growth. The TAA1-regulated local auxin biosynthesis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
230
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(240 citation statements)
references
References 91 publications
5
230
0
3
Order By: Relevance
“…Under control conditions (−Al), GUS staining was observed between ∼300 μm and ∼1 mm from the root tip (Fig. 2D), a region encompassing the root distal transition zone (RDTZ) and the root elongation zone (REZ), a demonstrated target for Al toxicity (22). GUS staining was also observed in the stele in more mature root regions where root hairs had emerged (Fig.…”
Section: Nip1;2 Expression In Roots Is Rapidly and Specifically Enhanmentioning
confidence: 90%
See 1 more Smart Citation
“…Under control conditions (−Al), GUS staining was observed between ∼300 μm and ∼1 mm from the root tip (Fig. 2D), a region encompassing the root distal transition zone (RDTZ) and the root elongation zone (REZ), a demonstrated target for Al toxicity (22). GUS staining was also observed in the stele in more mature root regions where root hairs had emerged (Fig.…”
Section: Nip1;2 Expression In Roots Is Rapidly and Specifically Enhanmentioning
confidence: 90%
“…The cell wall in the root rip region has been recognized as a major target for Al toxicity in plants (22,31,32). It has been suggested that the swollen and distorted root tip cells under Al stress are due, at least in part, to disruption of the cell wall structure, integrity, and function (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ethylene, auxin, and cytokinin have been reported to regulate the Al-induced inhibition of root growth (Massot et al, 2002;Sun et al, 2010;Yang et al, 2014). Ethylene can affect either auxin biosynthesis or auxin transport (Sun et al, 2010) in the root apex in response to Al stress.…”
Section: Discussionmentioning
confidence: 99%
“…Seedlings were grown hydroponically as described by Yang et al (2014) at pH 5.0 in a growth chamber with a 16-h-light/8-h-dark cycle at 22°C.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation